Applications of chaotic systems in steganography algorithms - Tuncer, Turker (ISAST: International Society for the Advancement of Science and Technology, 2017)
Chaotic systems are used in many information security applications due to their rich features. One of these application areas is steganography. In this study, a new CRT based chaotic steganography application is proposed and chaotic steganography algorithms have been examined.
10th International Conference on Chaotic Modeling and Simulation, CHAOS 2017 -- 30 May 2017 through 2 June 2017 -- Barcelona -- 151090
Keywords: Chaos; Computer science application; Steganography